Optimalisasi Acceptance and Commitment Therapy dengan Falsafah Nrimo Ing Pandum bagi Anak Panti Asuhan - Aqilah Syahira; Azizah Fitri Syariefah; Berliana Shafira; Sofia Rahma; Bani Bacan Hacantya Yudanagara (Buletin Riset Psikologi dan Kesehatan Mental, 2026)
Children in orphanages face psychological problems in the form of low self-acceptance and future optimism. This study aimed to optimize Acceptance and Commitment Therapy (ACT) by integrating the Javanese philosophy of Nrimo Ing Pandum. The method used was mixed-method approach through literature review, expert interviews, and quasi-experimental one-group pre-test post-test design using the Acceptance and Fusion Questionnaire for Youth (AFQ-Y). Preliminary findings showed alignment between the values of Nrimo Ing Pandum and ACT, including life acceptance, self-awareness, emotional regulation, and actions based on personal values. These values were developed into the PONDASI intervention handbook consisting of 6 sessions over 2 weeks. A trial involving 29 orphanage children showed a significant difference in AFQ-Y scores (t(28) = 4.05, p <.001, d = 0.75), indicating reduced experiential avoidance and potentially increased self-acceptance and optimism. These findings suggest that the intervention was effective and has potential as a culturally based psychological model.